Quality of Instagram Vlapictura as Information Media: Kualitas Instagram Vlapictura sebagai Media Informasi - Risna Hapsari Putriani; Ainur Rocmaniah (Academia Open, 2024)
This study employs a quantitative descriptive method to assess the effectiveness of Instagram as a communication medium for Vlapictura, a service-oriented business. With a population of 3018 Instagram followers, 96 respondents were sampled using a questionnaire-based data collection technique. The research focuses on evaluating the quality of use, information, interaction, and overall impression of Vlapictura's Instagram presence. The findings reveal that Vlapictura excels in the quality of use and performs exceptionally well in terms of information, interaction, and overall impression. This study contributes valuable insights into the efficacy of Instagram for service businesses, emphasizing its role in enhancing communication and engagement. Highlights : Strategic Use of Instagram: The study emphasizes the strategic utilization of Instagram as a powerful communication medium for businesses in the service sector. Quality of Interaction: Findings underscore the importance of maintaining high-quality interaction on Instagram to enhance overall impressions and engage effectively with the audience. Efficacy of Social Media Marketing: The research provides valuable insights into the effectiveness of Instagram as a marketing tool, particularly for service-oriented businesses, shedding light on its impact on communication and customer engagement. Keywords: Instagram, Service Sector, Business Communication, Social Media Marketing, Quantitative Analysis